The Last Argentine Military Dictatorship. Problems and Controversies: Between Historiography and Public and Politic Debates - Aguila, Gabriela (Hispania Nova, 2026)
The last military dictatorship has been a widely present topic since the democratic transition until today, both in public and political debate and in historiographic reflection and production. Its study and interpretation has gone through different moments and has been influenced by the complex situations experienced by the country from the recovery of democracy up to the most recent years, by the controversies in the public and political sphere and the changes in the social perception of the period, by the development of the process of memory, truth and justice, as well as by the rhythms of historiographic production. This article presents a critical and updated balance of the studies on the last dictatorship, identifying problems, debates and interpretations, seeking to put into dialogue with the changing contexts of the last decades.
Keywords: military dictatorship; Argentina; historiography; debates